2016
DOI: 10.1002/pd.4936
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of techniques for multiple platform testing in small, precious samples such as human chorionic villus sampling

Abstract: Background Multiple testing to understand global changes in gene expression based on genetic and epigenetic modifications is evolving. Chorionic villi, obtained for prenatal testing, is limited, but can be used to understand ongoing human pregnancies. However, optimal storage, processing and utilization of CVS for multiple platform testing has not been established. Results Leftover CVS samples were flash-frozen or preserved in RNAlater. Modifications to standard isolation kits were performed to isolate quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…CVS were processed as previously described [ 27 ]. Briefly, CVS tissue was thawed on ice with 600 μl of RTL Plus lysis buffer (QIAGEN) and 1% β-mercaptoethanol added to each sample.…”
Section: Methodsmentioning
confidence: 99%
“…CVS were processed as previously described [ 27 ]. Briefly, CVS tissue was thawed on ice with 600 μl of RTL Plus lysis buffer (QIAGEN) and 1% β-mercaptoethanol added to each sample.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, a recent study reported lower DNA yields in chorionic villi collected in RNA-later compared to snap frozen samples. 24 During sample processing we did notice a harder consistency of RNA-later tissues which rendered manual homogenization more difficult, with this difference being more noticeable in larger surgical tumor fragments (compared to biopsy specimens), which may explain their lower DNA and RNA yields. Lower RNA yields observed in RNAlater compared to freshly snap frozen samples are consistent with our previous observations in liver specimens.…”
Section: Discussionmentioning
confidence: 89%
“…Tissue samples (5-15 mg) were stored with 250 μl RNA later RNA Stabilization Reagent (QIAGEN, Hilden, Germany) at −80°C in the CSMC Prenatal Repository until further processing. Tissue was processed as previously described [58]. Briefly, tissue was thawed on ice with 600 μl of RLT Plus lysis buffer (QIAGEN) and 1% β-mercaptoethanol added to each sample.…”
Section: Methodsmentioning
confidence: 99%